Od kulturowego pojmowania przestrzeni ku rozważaniom o wieczności. Dyskurs przestrzenny w powieści Brisbane Jewgienija Wodołazkina - Sidor, Monika (Studia Rossica Posnaniensia, 2021)
This article deals with different aspects of space in the text of Eugene Vodolazkin’s novel Brisbane as well as in its studies and reception. Successive parts of the research are devoted to lieux de mémoire in autobiographical fiction, cultural understanding of the space of the home and places which traditionally create the image of Kiev and the individual mythology of this city. Space perceived in the way modified by culture is a certain frame in which both the hero of Vodolazkin lives and a receiver reads the novel. It is also an important component of the work’s internal structure, the factor responsible for certain genre associations that determine the direction of the reading process. In all these forms of functioning, space is thematically related to the reflection on death. The author concludes that the understanding of space leads to the rejection of the physical future and the affirmation of eternity understood in a religious way, in line with medieval tradition.